Does “Could” Lead to Good? On the Road to Moral Insight - Zhang, Ting; Gino, Francesca; Margolis, Joshua D. (Academy of Management Journal, 2018)
Dilemmas featuring competing moral imperatives are prevalent in organizations and are difficult to resolve. Whereas prior research has focused on how individuals adjudicate among these moral imperatives, we study the factors that influence when individuals find solutions that fall outside of the salient options presented. In particular, we study moral insight, or the discovery of solutions, other than selecting one of the competing moral imperatives over another, that honor both competing imperatives or resolve the tension among them. Although individuals intuitively consider the question "What should I do?" when contemplating moral dilemmas, we find that prompting people to consider "What could I do?" helps them generate moral insight. Together, these studies point toward the conditions that enable moral insight and important practical implications.